Polemic on sharia tourism between Muslim and Christian in Indonesia - Hapsin, Abu (HTS teologiese studies, 2023)
This article aimed to highlight how polemic between Muslims and Christians on halal tourism is discussed in Indonesia. The study concerned three research questions: How do Christians view halal tourism? Is the halal tourism a term that has the potential to build segregation according to the Christians’ perspective? How do Muslims respond to Christians on halal tourism? By reviewing related literature and conducting interviews and analysis using reception theory, this study reached the following conclusions. Firstly, Christian religious figures view on halal tourism by varied characters: realistic, substantial and critical. Secondly, for those with oppositional views, they emphatically said that the term halal tourism had the potential to build segregation. Meanwhile, in a negotiation position, the main substantial one is still open minded for discussion if there is a concept that is formally more inclusive and from the material side representing the common will even though it was originally a will of a particular group. Thirdly, Muslims, as represented in the Indonesian Ulema Council (MUI), perceive that halal tourism does not interfere with other religious beliefs, but it has an economic value for the country.Contribution: Practically, this article contributed to opening opportunities for halal tourism to be recognised by all elements in a multi-religious society. Differences in potential reception occur because the sender of the message and the recipient of the message have basic assumptions according to their respective contexts.